(untitled) (مجلة جامعة حماة, 2024)
The aim of the study was to conduct a field survey on the extent of the presence of diclazuril residues in the muscles and organs of marketed broilers in the governorate of Deir Ezzor. 72 samples were collected from four different areas in the city, divided into 24 samples from each organ or tissue in each area, with six samples for each organ from every region. Diclazuril residues were extracted from the samples and the remainder was analyzed using high-performance liquid chromatography at a wavelength of 280 nm, a flow rate of 1 ml per minute, and a temperature of 40 degrees Celsius using a C18 type separation column and a mobile length consisting of acetonitrile and ammonium acetate containing 0.01 mol/L tetrabutylammonium hydrogen sulfate, Prepared with a mixing ratio of (43/57).The results obtained indicate that out of 72 samples collected from the study areas, there were 48 samples (68.06%) that showed positive for the presence of diclazuril residues. All samples from the first area, whether muscle, stomach, or liver, were positive for the presence of diclazuril residues. The highest concentration detected was in liver samples (1900.71) and the lowest concentration in positive samples was stomach organelle samples (1.16 µg/kg live weight). Comparing the concentrations of diclazuril residues to the maximum residues limit according to the Codex Alimentarius, all concentrations were below the permissible limit (500 and 3000 µg/kg body weight in muscle tissue and liver, respectively). Key words: Diclazuril, broiler, residues, muscles, internal organs